POTENSI DAYA TARIK WISATA BATIK KUJUR DI KABUPATEN MUARA ENIM - Ristia Selviyanti; Jusmawi Bustan; A. Jalaludin Sayuti (Politeknik Negeri Sriwijaya, 2020)
This study aims This research aims to determine the Potential Tourism Attraction of Kujur Batik in Muara Enim Regency. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, documentation and literature study. The research location is at the Kujur Batik Industry Center, Tanjung Enim Hamlet, Tanjung Enim Village. The results show that the typical Tanjung Enim Batik art craft had a large enough potential to be developed into a tourist destination or attraction because it met the dimensions of tourist attraction which include aspects of uniqueness, beauty, rarity, seasonality, sensitivity, accessibility and social function. . As for the obstacles in the development of Batik Kujur to become a tourist attraction, namely in the aspect of high prices, the cost of shipping raw materials and mambatik equipment that is still sent from outside the region, besides the lack of human resources, one of the efforts needed to overcome this is procurement raw materials and equipment for batik to the region as well as the continuous empowerment of human or community resources through training and socialization on tourism so that people understand better the importance of the sustainability of the Kujur Batik handicraft and its potential attractivenessThis study aims This research aims to determine the Potential Tourism Attraction of Kujur Batik in Muara Enim Regency. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, documentation and literature study. The research location is at the Kujur Batik Industry Center, Tanjung Enim Hamlet, Tanjung Enim Village. The results show that the typical Tanjung Enim Batik art craft had a large enough potential to be developed into a tourist destination or attraction because it met the dimensions of tourist attraction which include aspects of uniqueness, beauty, rarity, seasonality, sensitivity, accessibility and social function. . As for the obstacles in the development of Batik Kujur to become a tourist attraction, namely in the aspect of high prices, the cost of shipping raw materials and mambatik equipment that is still sent from outside the region, besides the lack of human resources, one of the efforts needed to overcome this is procurement raw materials and equipment for batik to the region as well as the continuous empowerment of human or community resources through training and socialization on tourism so that people understand better the importance of the sustainability of the Kujur Batik handicraft and its potential attractiveness.